INTRODUCING JUSTICE START UP IN LABOR LEGAL CONTEXT - Rifka Yudhi (PRANATA HUKUM, 2021)
After graduating from college, almost all fresh graduates usually experience adilemma caused by the limitations or suitability of their competencies andopportunities, coupled with the presence of the Covid-19 pandemic. The commonopportunities chosen by fresh graduates include waiting for the momentum of the CPNS test, selecting BUMN employees, becoming private employees, and continuing their studies to the S2 level. However, this is not the case for Start Upwhich is barely even an option. The results of the discussion show that: (1) The increasing number of internet users in Indonesia, aspects of cost flexibility and ease of place, and starting to replace certain jobs either by applications or robots, should be able to be glimpsed by the younger generation who have lots of ideas and creativity in their fields to start a business up; (2) The start-up that is initiated must be fair and at least meet 3 (three) criteria: (i) the work relationship is based on a work agreement; (ii) The substance of the work agreement must include the type of work agreement, when it starts and ends, whether there is a probation period, work / tasks to be performed and responsibilities, the position given (if any), the amount of wages, facilities available, and rights. and other obligations, including when the employmentrelationship ends; (iii) efforts will be made to make efforts to meet decent livingstandards. work / tasks to be performed and responsibilities, the position given (if any), the amount of wages, facilities available, and rights. and other obligations, including when the employment relationship ends; (iii) efforts will be made to make efforts to meet decent living standards. work / tasks to be performed and responsibilities, the position given (if any), the amount of wages, facilities available, and rights. and other obligations, including when the employment relationship ends; (iii) efforts will be made to make efforts to meet decent living standards.